Policy Debate | Education and Employment Mismatch - Mona Mourshed; Tom Isherwood; Ali Jaffer; Cheryl Lim; Beatriz Cardoso; Shailaja Fennell; Claudio de Moura Castro (Revue Internationale de Politique de Développement)
Editor’s note: These papers are contributions to the ‘Policy Debate’ section of International Development Policy. In this section, academics, policy-makers and practioners engage in a dialogue on global development challenges. Papers are copy-edited but not peer-reviewed. Instead, the initial thematic contribution is followed by critical comments and reactions from scholars and/or policy-makers.Authored by McKinsey’s research team, the initial paper addresses the Education to Employment challenge. It is based on McKinsey’s study, which looked at skill development in 25 different countries and investigated education-to-employment initiatives. The authors claim that the most successful efforts are those where different stakeholders interact intensively and frequently. Employers need to get involved in education, and educators should play a bigger role in employment.The paper is followed by critical comments by tree authors : Beatriz Cardoso, Executive Director of Laboratório de Educação, Brazil, Shailaja Fennell lecturer at the Centre of Development Studies, University of Cambridge, UK, and Claudio de Moura Castro, economist, Brazil.This debate can be pursued on the Journal’s blog http://devpol.hypotheses.org/423.